Arguing about the mind - Gertler, Brie; Shapiro, Lawrence A. (Routledge, 2007)
Arguing About the Mind is an accessible, engaging introduction to the core questions in the philosophy of mind. This collection offers a selection of thought-provoking articles that examine a broad range of issues from the mind and body relation to animal and artificial intelligence. Topics addressed include: